2018
DOI: 10.1093/jxb/erx455
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy is activated and involved in cell death with participation of cathepsins during stress-induced microspore embryogenesis in barley

Abstract: Autophagy is activated and plays a role in stress-induced cell death during microspore embryogenesis, along with cathepsin-like C1A protease activities. Autophagy inhibition reduces cell death, improving embryogenesis induction efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 65 publications
2
51
0
Order By: Relevance
“…In a recent report, together with ROS production, we have demonstrated activation of autophagy after the inductive stress of microspore embryogenesis in barley. 20 Interestingly, key autophagy genes, particularly HvATG5 and HvATG6, were upregulated in microspore cultures after the stress treatment to induce embryogenesis. 20 Our results showed that barley stress-treated microspores showed an increase in the presence of autophagosomes and autophagic bodies, which exhibited specific immunofluorescence labeling with antibodies against ATG5 20 and ATG8 29,30 (provided by M.F.…”
Section: Stress-induced Microspore Cell Death Is Accompanied By Ros Pmentioning
confidence: 97%
See 1 more Smart Citation
“…In a recent report, together with ROS production, we have demonstrated activation of autophagy after the inductive stress of microspore embryogenesis in barley. 20 Interestingly, key autophagy genes, particularly HvATG5 and HvATG6, were upregulated in microspore cultures after the stress treatment to induce embryogenesis. 20 Our results showed that barley stress-treated microspores showed an increase in the presence of autophagosomes and autophagic bodies, which exhibited specific immunofluorescence labeling with antibodies against ATG5 20 and ATG8 29,30 (provided by M.F.…”
Section: Stress-induced Microspore Cell Death Is Accompanied By Ros Pmentioning
confidence: 97%
“…Previous reports that analyzed the possible role of certain cell death-related proteases in the stress response of the microspores have revealed that cathepsin L/F-, B-and H-like activities were induced after stress; concomitantly, cathepsin-like genes HvPap-1 and HvPap-6 were up-regulated. 20 The use of specific antibodies against HvPap-1 and HvPap-6 cysteine-proteases in western and immunofluorescence assays has shown not only that cathepsin gene expression and enzymatic activity increased but also that the proteins increased in microspores after the stress. 20 Our results using anti-HvPap-1 20 antibodies (provided by I. Díaz, CBGP-UAM, Montegancedo, Spain) in immunofluorescence assays analyzed by confocal microscopy, showed that cathepsins increased in stress-treated microspores and localized in small cytoplasmic rounded areas ( Figure 3G, H activity was also analyzed in microspore cultures and results showed similar kinetics to that of C1 cysteine proteases, with a marked increase in proteolytic activity after the stress treatment to induce embryogenesis.…”
Section: Stress-induced Microspore Cell Death Is Accompanied By Ros Pmentioning
confidence: 99%
“…In addition, it has been recently suggested that the autophagy pathway might promote PCD during microspore embryogenesis in barley. After a stress treatment at 4°C, autophagosome formation was visible in microspores along with PCD, and treatment with autophagy inhibitors decreased microspore cell death (Bárány et al, 2018). Vacuolar cell death through VPE in BY-2 cells treated with aluminum has been reported (Kariya et al, 2013; Kariya et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, autophagic cell death, which is regarded as one of the major PCD types, has been well studied in animals, including in C. elegans and D. melanogaster (Martin et al , ; Samara et al , ; Mariño et al , ). In plants, PCD and autophagy are usually found simultaneously in various cellular responses, like pathogen‐induced hypersensitive response (Xu et al , ), leaf senescence (Ono et al , ), xylem fiber development (Courtois‐Moreau et al , ) and microspore embryogenesis (Bárány et al , ). Additionally, emerging evidence suggests that autophagy is involved in the regulation of PCD during plant sexual reproduction (Minina et al , ; Xu et al , ).…”
Section: The Roles Of Autophagy In Key Processes Of Plant Reproductionmentioning
confidence: 99%
“…Nevertheless, autophagy and PCD are often considered as two disconnected events in plant reproduction. Recently, potential crosstalk between autophagy and PCD in plant sexual reproduction has often been speculated and discussed, although the detailed working mechanisms have not been well explored (Minina et al , ; Bárány et al , ).…”
Section: Introductionmentioning
confidence: 99%